How to be 21st century librarian / Hafawati Husna Mohamed Khairudin and Nor Adaviah Mohd Sabri - Mohamed Khairudin, Hafawati Husna; Mohd Sabri, Nor Adaviah (Faculty of Information Management, 2015)
This article discussed about the roles of librarians early and how to be 21st century librarian. It is important to the librarians because they have to survive in the new era of information because there are many changes and new thing in today's library era. Besides, they also need to change and renew their skills and expertise in order to expand their knowledge towards the library. Furthermore, the library's management also has to take part in teaching or training their librarians along with the development of their library. With that, the user can be more attracted with library and can get along with the staff whenever they need their help.